AUDIT INVESTIGASI KERUGIAN KEUANGAN NEGARA DALAM PENYIMPANGAN PENGELOLAAN DANA DESA DI KECAMATAN DUSUN SELATAN KABUPATEN BARITO SELATAN KALIMANTAN TENGAH - Tirtakusuma, Andreas Eno (ITB AAS Indonesia Surakarta, 2024)
The main use of Village Funds is directed for community development and empowerment projects, including the development of basic services: education, health, infrastructure and basic needs. Its effective management is an integral part of overall village financial management in the Regional Revenue and Expenditure Budget (APBD). Transparency and accountability are very important considering the potential for abuse such as Village Fund corruption cases. In Dusun Selatan District, South Buntok Regency, Central Kalimantan Province, there are 24 villages where part of the Village Fund is set aside and collected as participation in the establishment of Village-Owned Enterprises (BUMDes), with the business name: